Study of Protozoa population in wastewater treatment plants by image analysis - Motta, Maurício da (2001)
Protozoa are important microorganisms taking part to the ecosystem balance in wastewater treatment plants. A procedure for their semi-automated identification and counting based on image analysis is proposed. The main difficulty is the segmentation of the protozoa as most of them are in contact with the sludge. The protozoa are characterized by the size of their silhouette (area and length) and three shape factors (elongation, circularity and eccentricity). They are identified after projecting the resulting 5D space into a 3D space of principal components. The rate of automated identification is actually higher than 50% for some of the species commonly found in activated sludge.